(untitled) (International Journal of Geoscience, Engineering and Technology, 2022)
Against the current epidemiological situation caused by the new coronavirus (SARS-CoV-2), the world faces one of the biggest pandemics in the history of humanity, with that, vaccines have become something of great social interest. The storage of these immunobiologicals has become something of paramount importance to ensure their quality and effectiveness. The heat or temperature change accelerates the inactivation of immunogenic components, that way, it is possible to cause adverse events in breach of quality standards. Therefore, it is necessary to keep vaccines refrigerated at the recommended temperature, using instruments that ensure the quality of medicines from production to the vaccination room. The main objective of the present work is to use the Arduino platform as a practical and low cost sensor for monitoring and controlling the temperature of conservation and storage of Oxford/Astrazeneca and Coronavac vaccines, used in the figth against COVID-19, in order to accurately meet the temperature range of conservation between 2ºC and 8ºC seen as ideal by health agencies.